Novel Plastid-Nuclear Genome Combinations Enhance Resistance to Citrus Canker in Cybrid Grapefruit - Murata, Mayara M.; Omar, Ahmad A.; Mou, Zhonglin; Chase, Christine D.; Grosser, Jude W.; Graham, James H. (Frontiers in Plant Science, 2019)
Host disease resistance is the most desirable strategy for control of citrus canker, a disease caused by a gram-negative bacterium Xanthomonas citri subsp. citri (Xcc). However, no resistant commercial citrus cultivar has been identified. Cybridization, a somatic hybridization approach that combines the organelle and nuclear genomes from different species, was used to create cybrids between citrus canker resistant ‘Meiwa’ kumquat (Fortunella crassifolia Swingle snym. Citrus japonica Thunb.) and susceptible grapefruit (Citrus paradisi Macfad) cultivars. From these fusions, cybrids with grapefruit nucleus, kumquat mitochondria and kumquat chloroplasts and cybrids with grapefruit nucleus, kumquat mitochondria and grapefruit chloroplasts were generated. These cybrids showed a range of citrus canker response, but all cybrids with kumquat chloroplasts had a significantly lower number of lesions and lower Xcc populations than the grapefruit controls. Cybrids with grapefruit chloroplasts had a significantly higher number of lesions than those with kumquat chloroplasts. To understand the role of chloroplasts in the cybrid disease defense, quantitative PCR was performed on both cybrid types and their parents to examine changes in gene expression during Xcc infection. The results revealed chloroplast influences on nuclear gene expression, since isonuclear cybrids and ‘Marsh’ grapefruit had different gene expression profiles. In addition, only genotypes with kumquat chloroplasts showed an early up-regulation of reactive oxygen species genes upon Xcc infection. These cybrids have the potential to enhance citrus canker resistance in commercial grapefruit orchards. They also serve as models for understanding the contribution of chloroplasts to plant disease response and raise the question of whether other alien chloroplast genotypes would condition similar results.